Pragmatic Movements of Theravāda Buddhism in Nepal - Janak, Shramanera (Journal of Buddhist Studies (T.U.), 2025)
Buddhism demonstrates a tremendous capacity for pragmaticism, which allows it to coexist with current religions. This study demonstrates how it works on behalf of Theravada Buddhism in Nepal. However, the Theravada tradition in Nepal is still in its early stages, therefore comparisons with other Theravada countries are inappropriate. But how did it become a big Buddhist sect in Nepal? This study’s data was collected using both an ethnographic and descriptive method. The monks’ existence and various undertakings closely resemble practices found in other Theravada communities. Nonetheless, there is a tendency to incorporate practical methods, such as the well-established Newar traditions of interim ordination, as long as they do not violate the ideals of Theravada Buddhism. The rising interest in Newar culture and literature is inextricably linked to the Theravada mission within the Newar community, and it is beginning to attract attention from other ethnic groups as well. The significance of this study is to demonstrate the adaptability of Buddhism and pragmatic movements in establishing brand new religious communities in a short period of time.